2023
DOI: 10.1111/hel.12957
|View full text |Cite
|
Sign up to set email alerts
|

Mistakes in the diagnosis and treatment of Helicobacter pylori infection in daily clinical practice

Abstract: Background: An adequate diagnostic and therapeutic approach to Helicobacter pylori (H. pylori) infection is the cornerstone to avoid overdiagnosis, overuse of health resources, and increase in antibiotic resistances. The aim of the study was to evaluate the most common errors in clinical practice and the associated risk factors. Materials and Methods:This is a retrospective observational study including patients with H. pylori infection and no previous treatment belonging to two defined areas of the National H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In a recent study evaluating prescriptions for H. pylori eradication in Spain, a high-CLA country where PBMT is currently recommended as the first-line regimen, there was an overuse of levofloxacin as the first-line regimen (7.5%) and clarithromycin as the second-line regimen (2.6%). 5 Another study conducted in China reported that the status of prescribing eradication regimens containing antibiotics with high resistance rates was even more alarming. 6 Regarding first-line treatment, 17.5% of physicians used at least one antibiotic with a high resistance rate in triple therapy, and 11.2% used two antibiotics with high resistance rates in quadruple therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent study evaluating prescriptions for H. pylori eradication in Spain, a high-CLA country where PBMT is currently recommended as the first-line regimen, there was an overuse of levofloxacin as the first-line regimen (7.5%) and clarithromycin as the second-line regimen (2.6%). 5 Another study conducted in China reported that the status of prescribing eradication regimens containing antibiotics with high resistance rates was even more alarming. 6 Regarding first-line treatment, 17.5% of physicians used at least one antibiotic with a high resistance rate in triple therapy, and 11.2% used two antibiotics with high resistance rates in quadruple therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study evaluating prescriptions for H . pylori eradication in Spain, a high‐CLA country where PBMT is currently recommended as the first‐line regimen, there was an overuse of levofloxacin as the first‐line regimen (7.5%) and clarithromycin as the second‐line regimen (2.6%) 5 . Another study conducted in China reported that the status of prescribing eradication regimens containing antibiotics with high resistance rates was even more alarming 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies propose that CD may interfere with the normal mineralization of dental enamel, resulting in structural abnormalities [ 16 ]. Enamel defects, such as pitting, grooving, and discoloration, have been reported in individuals with CD, providing potential oral markers for the condition [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%